The Impact of Collaborative Inclusive Training Management (KOLIN) Through an Andragogical Approach on Enhancing the Competence of Islamic Boarding School Caregivers - Deden, S; Sudiapermana Elih; Rahmat Joni (The International Journal of Education Management and Sociology, 2025)
This study aims to analyze the impact of Collaborative Inclusive Training Management (KOLIN) using an andragogical approach to improve the competencies of Islamic boarding school caregivers. The andragogical approach was chosen due to its suitability for adult learners, such as pesantren caregivers, who possess different learning experiences and needs compared to traditional students. The KOLIN model emphasizes collaboration and inclusivity in training, allowing caregivers to share experiences, enhance pedagogical skills, and improve leadership and managerial capabilities in pesantren management. This research employs a qualitative approach with a case study design at several pesantren that have implemented the KOLIN training model. Data were gathered through in-depth interviews, observations, and document analysis of training implementation and its effects on caregiver competence. The results suggest that KOLIN training management through an andragogical approach significantly enhances teaching abilities, managerial skills, and understanding of innovative and inclusive teaching methods. These findings propose that adopting collaborative and inclusive training management is an effective strategy to develop the competencies of pesantren caregivers. Consequently, this study recommends that the KOLIN training model be adopted more widely, supported by adequate policies and resources to improve the quality of education in Islamic boarding schools.